Reversal of warfarin anticoagulation using prothrombin complex concentrate at 25 IU kg−1: results of the RAPID study. Issue 1 (7th October 2016) - Appleby, N.; Groarke, E.; Crowley, M.; Wahab, F. A.; McCann, A. M.; Egan, L.; Gough, D.; McMahon, G.; O'Donghaile, D.; O'Keeffe, D.; O'Connell, N.
SUMMARY: Background: Real‐world studies of the emergency reversal of warfarin using 4‐factor prothrombin complex concentrate (PCC) report unwarranted delays. The delay to receiving PCC was ≥ 8 h in 46·7% of patients with warfarin‐associated bleeding (PWAB) treated with a variable PCC dosing protocol in our retrospective audit. Objective: To report the impact of a simplified PCC dosing protocol on the interval to reversal of anticoagulation. Methods: We developed a PCC dosing protocol standardising the initial PCC dose and simplifying dosing calculations. Study end points were the proportion of PWAB achieving international normalised ratio (INR) ≤1·5 and treated within 8 h of presentation, respectively. Results: Of 17, 15 (88·2%) PWABs achieved a post‐treatment INR ≤ 1·5; 14 of 17 (82·4%) PWABs were reversed within 8 h. Median intervals between triage and PCC request and PCC request and start of infusion (administration interval) were 126 min (range 39–520) and 30 min (range 5–100), respectively. Compared with the retrospective cohort, RAPID is associated with an improved administration interval (mean 37·7 vs 76 min, P = 0·031) and the proportion of PWABs treated within 30 min (58·8 vs 6·7%, P = 0·009). Conclusion: The RAPID protocol reduces unwarranted delays without compromising efficacy.